Taxing in a Pandemic: An Assessment of the Impact of Covid-19 Pandemic on Tax Revenues and Revenues of Small and Medium Enterprises in Ghana. - Ntiamoah, Jones Adjei; Asare, Joseph; Arhenful, Peter; Owusu-Akomeah, Michael Nana (Archives of Business Research, 2023)
This study assessed the impacts of the COVID-19 pandemic on tax revenues and small and medium enterprise (SME) revenues in Ghana using qualitative and quantitative analysis. These impacts were analyzed using autoregressive tax regressions, buoyancy, and tax elasticity formulas. A simple radon sampling was used to select 350 SMEs in Ghana’s five major cities. Findings set out point to "demand" as a critical factor influencing SMEs’ sales and revenue with a rating of 5.3, a p-value less than the significance level of 0.05, and a deviation of 0.864, indicating the extent of the impact on tax revenue and sales of small and medium enterprises during a pandemic. In addition, a coefficient based on the ORL model application shows a value of 0.9565 in support of the econometric model used. The study also finds that tax revenue could drop by 8% and VAT revenue could drop by 1% or more. A tax buoyancy of 0.1% or 100% in forecasting tax revenue could be observed depending on the severity and impact of the pandemic. The findings show that tax revenue in a pandemic is adversely impacted, which requires logical and coordinated approaches to improve tax compliance.